ANALISA SUMBER DAYA, KEMAMPUAN, DAN KEUNGGULAN KOMPETITIF TERHADAP PT HINDO (H&M) INDONESIA - Syahara, Elvina; Thai, Kristina (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
A company certainly has a problem that can affect the success or success of acompany. Based on the analysis conducted by the author, several risk factors werefound that were faced by PT Hindo (H&M). Factors that influence success arestrategic decisions, resources, capabilities, core competencies, value chains andoutsourcing. But not only that, there are also many other things that are at risk forPT Hindo (H&M). The risk of this loss can become an obstacle to the path anddevelopment of a company. The methodology used in this article is that the authoruses the Observation and Internet Searching methodologies.Keywords: Factors of company success, Value Chain